Molecular modeling of S-RNases involved in almond self-incompatibility - Fernandez i Marti, Angel; Wirthensohn, Michelle; Alonso, Jose; Socias i Company, Rafael; Hrmova, Maria (Frontiers in Plant Science, 2012)
Gametophytic self-incompatibility (GSI) is a mechanism in flowering plants, to prevent inbreeding and promote outcrossing. GSI is under the control of a specific locus, known as the S-locus, which contains at least two genes, the RNase and the SFB. Active S-RNases in the style are essential for rejection of haploid pollen, when the pollen S-allele matches one of two S-alleles of the diploid pistil. However, the nature of their mutual interactions at genetic and biochemical levels remain unclear. Thus, detailed understanding of the protein structure involved in GSI may help in discovering how the proteins involved in GSI may function and how they fulfil their biological roles. To this end, 3D models of the SC (Sf) and two SI (S8 and S23) S-RNases of almond were constructed, using comparative modelling tools. The modelled structures consisted of mixed α and β folds, with six helices and six beta-strands. However, the self-compatible (Sf) RNase contained an additional extended loop between the conserved domains RC4 and C5, which may be involved in the manifestation of self-compatibility in almond.